2019
DOI: 10.1044/2019_ajslp-18-0275
|View full text |Cite
|
Sign up to set email alerts
|

Visual Analog Scale Ratings and Orthographic Transcription Measures of Sentence Intelligibility in Parkinson's Disease With Variable Listener Exposure

Abstract: Purpose While orthographic transcription (OT) is the gold standard for measures of intelligibility, it is relatively inaccessible to clinicians. This study investigates the relationship between visual analog scale (VAS) ratings and OT measures of intelligibility for speakers with Parkinson's disease (PD), with the eventual goal of developing more clinically feasible assessments of intelligibility. Method Twenty speakers with PD and 5 controls read 11 se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 36 publications
5
25
0
1
Order By: Relevance
“…In relation to the method used to measure speech intelligibility, the findings of this study are in agreement with several previous studies (Abur et al 2019, Stipancic et al 2016, Yorkston and Beukelman 1978. Differences in the intelligibility scores measured by the two methods may be related to the fact that measurement involving orthographic transcription provides a score reflecting only the number of spoken words recognised by the listener, whereas a rating task may also be sensitive to additional subjective listener judgements of speech features (Tjaden et al 2014a).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In relation to the method used to measure speech intelligibility, the findings of this study are in agreement with several previous studies (Abur et al 2019, Stipancic et al 2016, Yorkston and Beukelman 1978. Differences in the intelligibility scores measured by the two methods may be related to the fact that measurement involving orthographic transcription provides a score reflecting only the number of spoken words recognised by the listener, whereas a rating task may also be sensitive to additional subjective listener judgements of speech features (Tjaden et al 2014a).…”
Section: Discussionsupporting
confidence: 90%
“…The intelligibility scores in the current study were found to be highly correlated across both orthographic transcription and VAS tasks. These findings agree with those of Abur et al (2019) and Stipancic et al (2016). The strong positive correlation across tasks indicates that while scores differed, the general pattern of scores was similar.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations